(untitled) (The Pakistan Development Review, 2010)
Fiscal decentralisation refers to the transfer of authority and responsibility from central government to sub-national or the local government. It is mostly pre-assumed that fiscal decentralisation can play important role in the efficient allocations of resources and improvement of the political, economic and social activities. Many studies unlock the relationship between federal government and sub-national governments or local government. Fiscal decentralisation theories mostly based on Richard Musgrave’s (1939) functions of government. He defined three roles: stabilisation, allocation and distribution whereas, only the allocation function seems to be appropriate to fiscal decentralisation theory. Because these three functions are not equally suitable for all level of governments and it is necessary for efficiency that each function is properly matched to the level. It is a step forward towards more responsive and efficient governance if the decentralisation is done properly [Oates (1972)]. The logic behind fiscal decentralisation is accountability and efficiency; the smaller organisations are more fragile for accountability than the larger ones. However, decentralisation has not always been effective in the provision of service delivery and hardly accountable due to lack of community participation. If there is no spill over effects and in the absence of diseconomies of scale it could be effective and efficient. The sub-national governments where the externalities are internalised and scale economies are acceptable fiscal responsibilities should be assigned [Rodden, et al. (2003)]. The sub-national governments are much closer to the people and they are better informed to respond according to their demands of goods and services [Hayek (1945); Qian and Weingast (1997)]. Service deliveries are highly dependent on transfers from central governments. It is necessary to increase the revenue autonomy of sub-national governments and it is linked with the service delivery in social sector [Elhiraika (2007)]. Lower level of governments is closer to the people and much aware of the preferences of localities. Service deliveries should be located at the lowest level because decentralised provision of services increases the economic welfare [Oates (1999)].